2018
DOI: 10.1007/s11258-018-0814-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in primary production followed by rapid recovery of plant biomass in response to repeated mid-season droughts in a semiarid shrubland

Abstract: Reduction in primary production followed by rapid recovery of plant biomass in response to repeated mid-season droughts in a semiarid shrubland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Extreme drought effect was evident neither with Cropscan nor with Sequoia measurements. These results are compliance with major findings from the VULCAN/INCREASE experiment which revealed that recurring drought treatment (precipitation exclusion) leads to mid-season reduction of aboveground biomass [6]. This is coherent with the results obtained by using NDVI from multispectral Sequoia on board of UAV.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Extreme drought effect was evident neither with Cropscan nor with Sequoia measurements. These results are compliance with major findings from the VULCAN/INCREASE experiment which revealed that recurring drought treatment (precipitation exclusion) leads to mid-season reduction of aboveground biomass [6]. This is coherent with the results obtained by using NDVI from multispectral Sequoia on board of UAV.…”
Section: Discussionsupporting
confidence: 91%
“…Factors are controlled and effects are measured during a predetermined period or in few cases for the long run such as ANAEE [4] or Drought-Net [5]. At plot scale, climate manipulation experiments are a particularly effective way to study the ecological consequences of climate change [6]. However, they are normally conceived to collect measurements at a certain spatial scale, usually related to plot size or sampling method [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations